Twelve days of Christmas [compact disc, unabridged] : a novel - Macomber, Debbie (Random House Audio ; Books on Tape, 2016)
"Friendly and bubbly, Julia Padden likes nearly everyone, but her standoffish neighbor, Cain Maddox, presents a particular challenge. No matter how hard she's tried to be nice, Cain rudely rebuffs her at every turn, preferring to keep to himself. But when Julia catches Cain stealing her newspaper from the lobby of their apartment building, that's the last straw. She's going to break through Cain's Scrooge-like exterior the only way she knows how: by killing him with kindness. To track her progress, Julia starts a blog called The Twelve Days of Christmas. Her first attempts to humanize Cain are far from successful...Meanwhile, Julie's blog becomes an online sensation, as an astonishing number of people start following her adventures."--Publisher.